Spurious amplification of a Plasmodium vivax small-subunit RNA gene by use of primers currently used to detect P. knowlesi. - Imwong, M; Tanomsing, N; Pukrittayakamee, S; Day, N; White, N; Snounou, G (2009)
The PCR primers commonly used to detect Plasmodium knowlesi infections in humans were found to cross-react stochastically with P. vivax genomic DNA. A nested primer set that targets one of the P. knowlesi small-subunit rRNA genes was validated for specificity and for sensitivity of detection of <10 parasite genomes.